Fortines y pueblos en Buenos Aires del siglo XVIII. ¿Una política de urbanización para la frontera? - Canedo, Mariana (Centro de Historia Argentina y Americana, 2007)
Although the urban development in America was not exclusive of the European colonization, the foundation of towns and cities constituted a specific politics of conquest and colonial dominance. During the second half of the XVIII century and under the government of the Borbones, the politics established seemed to accompany the increase and growth of the cities and the towns in Spanish America, and to incentivate the urbanization of the areas of frontier of their Empire. Two queries articulate this work. Can the proposals formulated by the colonial authorities for Buenos Aires be located inside the urbanization politics proposed by the Borbones for frontier areas in Spanish America ? If this was this way, what concretion level has this politics had during the last decades of colonial bond? The establishment of towns will be studied for the case of Buenos Aires during the last decades of the XVIII century.